Credit limit : banks are turning their backs on money transfer outfits - Curwen, Lesley (2013)
Reports on the actions by banks to end the relationship with companies that provide money transfer services to avoid the risk of heavy fines if ill-gotten gains pass through their accounts. Notes that this action could leave migrants with no safe way to send money home to relatives.